Alloy scattering in quantum well wire structures of semiconductor ternaries - Ibragimov, G.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
We studied the effect of the alloy-disorder-scattering on the electron transport in a quasi-one-dimensional semiconductor. Performed were analytical calculations of the alloy-disorder-limited momentum relaxation time for carrier scattering in a cylindrical quantum wire using modeling wave functions, when the transverse part of the carrier wave function is taken as a Bessel function. It is found that the one-dimensional mobility is significantly greater than two-dimensional one. It is shown that the alloy-disorder-scattering-limited mobility increases with the increasing wire radius and increases with the increasing temperature. We compare our results with different scattering mechanisms for one-dimensional systems. Results are also included for the alloy composition dependence of the mobility.